Online Education Status at Dental Colleges During COVID-19 Pandemic in Nepal - Shrestha, R.M.; Shrestha, S.; Acharya, A.; Gupta, A. (Kathmandu University Medical Journal, 2020)
Background The COVID-19 pandemic has caused lockdown situation impeding all educational institutions including dental colleges. The circumstance demanded online classes as the alternative strategy for continuation of education. Objective To assess current practice and perception about online education among faculties of dental colleges in Nepal. Method A cross-sectional study was conducted among 208 faculties of all dental colleges in Nepal. Data collection was done through structured online questionnaire comprising demographic information, practice and perception of the respondents towards online education. Descriptive statistics surveyed the frequency distribution and Chi-square test assessed the difference in perception among the faculties of different universities. Result The response rate was 74.3%. Faculties commonly used PowerPoint presentation (96.6%) on Zoom platform (83.3%) using laptop (94.7%) with Wi-Fi connection (91.8%). Majority of faculties had good or satisfactory access to internet (94.8%). The faculties believed that the online class environment was interactive (95.2%); but it was not effective (86.5%) as live classroom. Majority of the faculties (79.4%) felt tracking of students’ presence was difficult. There was no significant difference on perception towards online class among the faculties of Kathmandu University, Tribhuvan University and BP Koirala Institute Health Sciences at p < 0.05. Conclusion The COVID-19 pandemic has paved the way for e-learning in dental education in Nepal. Faculties agree to complete the theory syllabus and conduct sessional exams as an alternative during the lockdown period. However, they show strong reservations in carrying out practical/clinical simulations and university exams online. Training on e-learning and institutional strategy for online education is recommended.